Another approach to the problem of the ruin probability estimate for risk process with investments - Androshchuk, M.; Mishura, Y. (Інститут математики НАН України, 2007)
An exponential estimate of ruin probability for an insurance company which invests all its capital in risk assets is found. The process which describes the risky assets is assumed to follow a geometrical Brownian motion. Insurance premium ﬂow depends on the value of reserves of the insurance company. The problem is solved by reduction of the generalized risk process to the classical risk process without investments.